Representasi Re-Experiencing, Avoidance, dan Hyperarousal of Mental Health dalam Novel Lanang - Lutfi Azizah Madya Gumelar; Yessy Hermawati (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2021)
Man can express the state of their souls through literary works, and Man also gain experience of their souls by reading and appreciating literary works. This paper aims to see a description of trauma symptoms related to the mental health of Lanang figures, in the Lanang Novel by Yonathan Rahardjo. The inner conflict of the characters in this novel represents the symptoms of trauma resulting in mental health disorders. It is important to know that novel readers can understand mental health issues through the appreciation of literary works. This novel study uses the contentanalysis method and literary psychoanalysis approach carried out to describe psychological problems, especially related to mental health disorders in Novel Lanang. The results of the analysis show that the symptoms of trauma can be shown through three things, namely: 1) Re-experiencing or intrusion is the reappearance of a traumatic event in the self (flashback), 2) Avoidance is an uncomfortable or painful feeling that makes him try to avoid so as not too experienced a traumatic event. 3) Hyperarousal is excessive anxiety experienced by sufferers causing him to feel in a state of being threatened or a constant danger. These three things are reflected in the character of Lanang. The description of trauma symptoms in this novel can be used as an initial experience to understand mental health issues. Literary works can also be a source of knowledge about the state of human psychology.